2022
DOI: 10.1038/s41415-022-4138-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral surgery wait times in NHS secondary dental care in England: a five-year review

Abstract: Aims To report the oral surgery referral to treatment waiting times in hospitals in England and to identify any trends in the percentage of patients seen within 18 weeks. Materials and methods Data published by the NHS statistics team was analysed from 2016-2020. Results Pre-COVID-19, the best performing month was February 2016, with 91.5% of patients seen within 18 weeks. The worst performing month was September 2019, with 79.3% of patients seen withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[29][30][31] Currently, NHs dental contract reform is being considered in all countries of the UK and increasing the use of hygienists and therapists (skill mix) is on the agenda. [32][33][34] increasing skill mix has previously been reported as having the potential to improve access to dental care, which may reduce inequalities. 29,35 This review found that being self-employed in this role was associated with job dissatisfaction, 19 however there has been no recent exploration of attitudes towards employment among this group of dental care professionals.…”
Section: Discussion Dental Hygienists and Dental Therapistsmentioning
confidence: 99%
“…[29][30][31] Currently, NHs dental contract reform is being considered in all countries of the UK and increasing the use of hygienists and therapists (skill mix) is on the agenda. [32][33][34] increasing skill mix has previously been reported as having the potential to improve access to dental care, which may reduce inequalities. 29,35 This review found that being self-employed in this role was associated with job dissatisfaction, 19 however there has been no recent exploration of attitudes towards employment among this group of dental care professionals.…”
Section: Discussion Dental Hygienists and Dental Therapistsmentioning
confidence: 99%